Factors of Service Quality in Customer Trust and Customer Loyalty of Bank Mandiri Panorama-Bengkel City Branch - Dennis Tambunan Rydarto; Kamelia Astuty; Andi Mulyono; Dewi harwini; Indra Utama (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study was conducted to determine the effect of service quality on customer satisfaction and loyalty on Mandiri-Bank of Panorama’s branch-Kota Bengkulu. The research location is on Jl. Salak Raya no.102-103, Lingkar Timur, Kecamatan Singaran Pati, Kota Bengkulu, 38225. The site selection was based on several considerations, namely Mandiri Bank of Panorama’s branch Bengkulu which is the branch office of the bank in Kota Bengkulu, samples taken are 150 people with purposive sampling method. Data collected by questionnaires by using a 5-point Likert scale to measure 24 indicators. The analysis technique used is path analysis. These results indicate that the service quality variable positive and significant impact on the customer’s trust, service quality variable positive and significant impact on customer’s loyalty, variable customer confidence positive and significant impact on customer’s loyalty, and service quality variables affect posiitif on customer’s loyalty through customer’s trust of Bank Mandiri namely Panorama’s Branch Kota-Bengkulu. Therefore, more better the quality of service more bigger the customer’s confidence, and, so forth the customer’s trust.